PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO BERBASIS PODCAST DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK DI KELAS V SEKOLAH DASAR - Anggraeni, Erlin Putri; Jamaludin, Ujang; Fajrudin, Lili (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to develop podcast-based audio learning media to improve fifth-grade students’ listening skills on figurative language (majas) in elementary school. The research employed a Research and Development (R&D) method using the ADDIE model. Previous studies have demonstrated the effectiveness of podcasts in enhancing listening skills, including an increase in average scores from 67.2 to 92 after the use of podcast-based learning, as well as findings that Google Podcasts facilitate better understanding of Indonesian language materials. The subjects of this study were 32 fifth-grade students at SD Negeri Cikande 1. Data were collected through interviews, observations, expert validation questionnaires, response questionnaires, and evaluation tests. The validation results indicated that the developed media was highly feasible, with scores of 95% from material experts, 95% from language experts, and 92% from media experts. Student responses reached 95.98%, and teacher responses reached 100%, both categorized as “very feasible.” In conclusion, podcast-based audio media is highly feasible and effective for improving students’ listening skills in Indonesian language learning at the elementary level.